2020
DOI: 10.26444/jpccr/126596
|View full text |Cite
|
Sign up to set email alerts
|

Fear of childbirth and sense of coherence with their determinants in endangered and healthy pregnancies

Abstract: Introduction. The growing number of Cesarean sections and the percentage of women dissatisfied with perinatal care are the one of the main problems of modern gynaecology in Poland. It seems that if women with a high fear of delivery and a low sense of coherence are scanned early enough, it can contribute to better psychological care and greater satisfaction while giving birth. Objective. The aim of the study is to compare the level of fear of childbirth and sense of coherence between endangered and healthy pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The results of bootstrapping in the present study showed that the direct effect of SOC in explaining CSE was significant. This finding is in agreement with the findings of a study which reported that SOC improvement can reduce women's fear over pregnancy and labor pain (17). Another study also showed the significant positive correlation of SOC with interest in vaginal delivery (19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of bootstrapping in the present study showed that the direct effect of SOC in explaining CSE was significant. This finding is in agreement with the findings of a study which reported that SOC improvement can reduce women's fear over pregnancy and labor pain (17). Another study also showed the significant positive correlation of SOC with interest in vaginal delivery (19).…”
Section: Discussionsupporting
confidence: 91%
“…SOC consists of different trainable skills such as realization, consciousness improvement, social health and subjective well-being promotion, creation of integrity and coherence, and openness to new experiences (16). SOC can reduce women's fear and anxiety over pregnancy and labor pain and improve their motivation for having vaginal delivery (17). Women with higher SOC are more willing to have vaginal delivery (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…There are studies showing that the fear of childbirth is higher in complicated pregnancies. 33,34 Moreover, a stronger fear of childbirth is also characteristic of women who view their previous childbirths as traumatic. 35 In our study, we found that the participants with negative previous childbirth experiences had higher levels of fear of childbirth and childbirth anxiety.…”
Section: Discussionmentioning
confidence: 99%